2012
DOI: 10.1186/1751-0147-54-75
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection in Norwegian dairy goats

Abstract: BackgroundToxoplasma gondii is a major problem for the sheep industry as it may cause reproduction problems. The importance of T. gondii in Norwegian goat herds is uncertain, but outbreaks of toxoplasmosis in dairy goat farms have been recorded. The aim of this study was to describe the prevalence of T. gondii infection in Norwegian dairy goats by using serology.FindingsGoat serum originally collected as part of two nationwide surveillance and control programmes between 2002 and 2008 were examined for T. gondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
1
7
0
2
Order By: Relevance
“…On the other hand, high farm prevalence rates are common. A study in Poland showed a 100% farm level with a 30-100% prevalence at the individual level (Czopowicz et al 2011), while in Norway, despite a 17% prevalence at the individual level, the farm prevalence was 75% (Stormoen et al, 2012) and a prevalence of 25.1% for animals and 72.2% for farms has been reported from Spain (Garcia-Bocanegra et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high farm prevalence rates are common. A study in Poland showed a 100% farm level with a 30-100% prevalence at the individual level (Czopowicz et al 2011), while in Norway, despite a 17% prevalence at the individual level, the farm prevalence was 75% (Stormoen et al, 2012) and a prevalence of 25.1% for animals and 72.2% for farms has been reported from Spain (Garcia-Bocanegra et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the seroprevalence of T. gondii in goats was estimated at 17% in Norway (Stormoen et al, 2012), 18.5% in north Portugal (Lopes et al, 2013), 30.7% in Greece (Tzanidakis et al, 2012), 25.1% in southern Spain (Garcia-Bocanegra et al, 2013), 52.8% in Romania (Iovu et al, 2012), and 60.6% in Italy (Mancianti et al, 2013). Regional variation of seroprevalence may be caused by differences in study population, study year and climate as well as differences in serological tests and criteria of cutoff value used in the test (Tenter et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a study in France conducted in 2007, the proportion of sheep carcases carrying live parasites was 5.4 % (3-7.5 %) and molecular typing mostly revealed genotype II (Halos et al, 2010). In a recent survey in Norwegian dairy goats, the seroprevalence was 17 %, and 75 % of herds were found to have at least one seropositive animal (Stormoen et al, 2012). Although isolation of T. gondii from caprine tissues has been reported, no large-scale prevalence data are available on the presence of this parasite in goat meat products (Kijlstra and Jongert, 2008).…”
Section: Current Situation and Trends In The Eumentioning
confidence: 99%